2017
DOI: 10.1002/hipo.22708
|View full text |Cite
|
Sign up to set email alerts
|

Sequential learning during contextual fear conditioning guides the rate of systems consolidation: Implications for consolidation of multiple memory traces

Abstract: Systems consolidation has been described as a time-dependent reorganization process involving the neocortical and hippocampal networks underlying memory storage and retrieval. Previous studies of our lab were able to demonstrate that systems consolidation is a dynamic process, rather than a merely passive, time-dependent phenomenon. Here, we studied the influence of sequential learning in contextual fear conditioning (CFC) with different training intensities in the time-course of hippocampal dependency and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Animals were housed in plastic cages, 4–5 per cage, under a 12 h light/dark cycle at a constant temperature of 24 °C, with water and food ad libitum. Sample size for each group ( n = 8–15) was estimated based on previous studies of our laboratory 16,17,19,20 . Animals were randomly assigned to treatment groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were housed in plastic cages, 4–5 per cage, under a 12 h light/dark cycle at a constant temperature of 24 °C, with water and food ad libitum. Sample size for each group ( n = 8–15) was estimated based on previous studies of our laboratory 16,17,19,20 . Animals were randomly assigned to treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we showed that fear generalization is closely related to hippocampal dependency during retrieval 16,17 ; we found that this structure is crucial to orchestrate the reconstruction of detailed memories 1618 . Environmental factors, such as sequential learning and training intensity, can accelerate hippocampal independency and memory generalization 17,19,20 . Evidence from animal studies shows that retrieval of recent contextual fear memory induces higher hippocampal activation than remote memories 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments indeed reported such a reorganization of brain circuitries, notably of mPFC taking over from the HPC in case of lesion before CFC encoding [57] or prolonged optogenetic inhibition at the time of recall [49]. In addition, the dynamics of consolidation could be modulated bidirectionally by either adding a novel learning event between the encoding and the recall of a CFC [95,96] or during a spatial learning task [97], which resulted in a faster memory dependance on cortical areas, or conversely by adding external factors, such as odors, to prolong the HPC dependency of a memory [98]. Moreover, the phenomenon of co-allocation of memories that are experienced close in time underlines the importance of the brain state at the time of learning [91,99].…”
Section: Memories Are Dynamic: Discussion and Outlookmentioning
confidence: 94%
“…We tested whether presenting an odor during fear conditioning, and then again during retrieval, would alter the dynamics of consolidation in a way that engaged the HPC for a longer period of time (e.g., high intensity training has been shown to have the opposite effect, speeding up the decay of HPC dependency promoting memory generalization; Pedraza et al 2017). We found that odor influenced this temporal relationship biasing the memory system away from the PFC and toward the HPC, suggesting that retrieval of highly contextual experiences does require the HPC even at remote time points.…”
Section: Discussionmentioning
confidence: 99%